"Talk about Chemistry": A Voluntary and Effective Integration among the Players of Teaching Chemistry - Adriana Vitorino Rossi (Athens Institute for Education and Research, 2016)
The "Talk about Chemistry" (TAC) reported here proposes an integrating action involving undergraduates, new and senior chemistry teachers and teacher educators. It is a 6h annual voluntary meeting to talk about current and stimulating chemistry topics and discuss how to teach and learn them. Short speeches are clear and accessible, in order to encourage the audience's participation. There is no passive role and all people involved express opinions, share experiences and act as educators as they discuss scientific and educational knowledge, teaching practice and professional qualification. These activities provide simultaneously initial training and the continuous education of chemistry teachers. The assessment of this proposal involved spontaneous oral statements and written reports, with positive remarks highlighting the importance of TAC, for teachers to share experiences, expectations, doubts and possible solutions. TAC requires very little resources and prior organization, but has a positive impact regarding the training of chemistry teachers.